Complex foraging behaviours in wild birds emerge from social learning and recombination of components - Wild, S; Chimento, M; McMahon, K; Farine, DR; Sheldon, BC; Aplin, L (Royal Society, 2021)
Recent well-documented cases of cultural evolution towards increasing efficiency in non-human animals have led some authors to propose that other animals are also capable of cumulative cultural evolution, where traits become more refined and/or complex over time. Yet few comparative examples exist of traits increasing in complexity, and experimental tests remain scarce. In a previous study, we introduced a foraging innovation into replicate subpopulations of great tits, the ‘slidingdoor puzzle’. Here we track diffusion of a second ‘dial puzzle’, before introducing a two-step puzzle that combines both actions. We mapped social networks across two generations to ask if individuals could: 1) recombine socially-learned traits, and 2) socially transmit a two-step trait. Our results show birds could recombine skills into more complex foraging behaviours, and naïve birds across both generations could learn the two-step trait. However, closer interrogation revealed that acquisition was not achieved entirely through social learning—rather, birds socially learned components before reconstructing full solutions asocially. As a consequence, singular cultural traditions failed to emerge, although subpopulations of birds shared preferences for a subset of behavioural variants. Our results show that while tits can socially learn complex foraging behaviours, these may need to be scaffolded by rewarding each component.